KOPING STRES DALAM MENJALANI PERAN GANDA PADA WANITA HINDU DI DENPASAR - Diputra, Nyoman Dita Wira; Lestari, Made Diah (Jurnal Psikologi Udayana; Vol 2 No 2 (2015)DO - 10.24843/JPU.2015.v02.i02.p09, 2015)
In Bali, Hindu women are not only demanded to perfom the roles of housewives and career women, but they also have responsibility towards their banjar and their religion. They play important roles in preparing for religious ceremonies that are done almost every day, which include preparing banten, metanding, atau majejahitan (Lanus, 2010). Hindu women that have a dual roles in the family have the potential to experience stress because they are demanded to perform their roles as, office employee, and have religious and social duties in the banjar, as well as their basic role as a housewive. Stress coping is needed to deal with stressful conditions. This study aims to see the stressors, types, symptoms, and stress coping experienced by Hindu women in Denpasar. This study used a qualitative method with a phenomenology design. The subjects used in this study were five Hindu women 25-35 years old, have been married with maximum primary school age children, have duties as a housewife and as a career woman, have activities in the banjar and pura. The result of this study showed that the stressors came from their families and environment. Generally, the types of stress that came from families were pressure and frustration with psychological symptoms and were emotional focused coping. Stress that came from the environment usually in the form of conflict and frustration. The symptoms could be psychological and biological, and the coping used may include emotional and problem focused coping.   Key Words: Hindu Women, Dual Roles, Stress and Stress Coping